Association between plasma complement factor H concentration and clinical outcomes in patients with sepsis. Issue 1 (19th January 2021) - Shimizu, Junji; Fujino, Kazunori; Sawai, Toshihiro; Tsujita, Yasuyuki; Tabata, Takahisa; Eguchi, Yutaka
Abstract : Aim: The complement system is important for defending against pathogens, however, excessive complement activation is associated with a poor prognosis and organ dysfunction in sepsis. Complement factor H (CFH) acts to prevent excessive complement activation and damage to the self through the regulation of the complement alternative pathway. We investigated the association between plasma CFH levels on admission to the intensive care unit (ICU) and 90‐day mortality, severity scores, and organ dysfunction in patients with sepsis. Methods: We assessed the relationship between the plasma CFH on admission to the ICU and 90‐day mortality, severity scores such as the Acute Physiology and Chronic Health Evaluation II score, Sequential Organ Failure Assessment score, and Simplified Acute Physiology Score 2, and organ dysfunction. Results: This analysis included 62 patients. The plasma CFH levels were significantly lower in 90‐day non‐survivors than in survivors (70.0 μg/mL [interquartile range, 51.2–97.6] versus 104.8 μg/mL [interquartile range, 66.8–124.2]; P = 0.006) . The plasma CFH levels were associated with 90‐day mortality (odds ratio 0.977; 95% confidence interval, 0.957–0.994; P = 0.01). The plasma CFH levels were negatively correlated with severity scores. The Sequential Organ Failure Assessment scores for the coagulation and neurological components were negatively correlated with the CFH concentration. Conclusion: Lower plasma levels of CFH were associated with increased severity and mortality in patients with sepsis on admission to the ICU and were correlated with central nervous system dysfunction and coagulopathy. Abstract : Plasma complement factor H levels were significantly lower in non‐survivors than in survivors and healthy controls.